Library service strategies to increase visiting interest of generation c in South Sulawesi - Hidayatullah, Fauzan; Rahman, Rosnani Abdul (Universitas Padjadjaran, 2025)
Background: Libraries play a vital role in disseminating knowledge and providing access to information. However, the declining interest of Generation C in traditional library visits highlights a pressing need for adaptive strategies aligned with their digital habits. While many studies focus on general digitalization efforts, limited research addresses how local public libraries respond to Generation C’s preferences in practice. Purpose: This study aimed to analyze strategic initiatives implemented by the Makassar City Library to enhance Generation C’s engagement and visitation rates. Methods: A qualitative case study approach was employed, with data collected through interviews, focus group discussions, and direct observations. Participants included librarians and active Generation C users, selected through purposive sampling to capture relevant and experience-based perspectives. Results: Findings revealed that Generation C values libraries with advanced digital and physical features, such as high-speed Wi-Fi, public-use computers and tablets, interactive and collaborative learning spaces, cafés, and access to digital collections. In response, the South Sulawesi Provincial Library and Archives Service has launched strategies including interactive social media outreach, the development of educational websites, and mobile digital library services through platforms such as Elfan and iSulsel. Redesigned physical spaces that encourage creativity and collaboration also proved attractive to younger users. Conclusion: These strategies demonstrate how libraries can remain relevant by embracing technology, user convenience, and participatory service design. They contribute to increasing Generation C's library visitation and engagement. Implications: Practically, the study highlights the importance of integrating digital infrastructure and spatial innovation to meet modern user expectations. Theoretically, it underscores how localized, user-centered strategies contribute to library relevance in the digital age, offering a model for other public libraries facing similar generational engagement challenges.